Multi-criteria sustainability performance measurement: An application in Cuba - Medel-González, Frank; Salomon, Valério A.P. [UNESP]; García-Ávila, Lourdes (Inderscience Publishers, 2015)
Sustainability has become a big challenge to address in organisations of all sectors. Demonstrate the organisations commitment, including environmental and social issues at management and decisions processes, is essential. The aim of this paper is to present a network model to measure corporate sustainability performance and its practical application. The model was developed using the combination of different managerial tools like balanced scorecard, performance measurements systems and strategic sustainable alignment matrix. Analytic network process and analytic hierarchy process as multi-criteria methods were combined in the model. The application in four medium-sized companies located in Cuba allows identifying critical issues and opportunities for improvement in relation with sustainability performance. Despite the recognised limitations in the model, it can be a useful tool for organisations.
Keywords: Corporate sustainability; MCDM; Multi-criteria decision making; Performance measurement